INISIASI MENYUSU DINI DAN PRODUKSI ASI PADA IBU POST PARTUM DI RSUD SOE TAHUN 2013 - SERAN, AGUSTINA ABUK (MIDWIFERY MEDICAL JOURNAL, 2014)
Breastfeeding the first hour of life begins with skin contact between mother and baby is declared as a global indicator.Result of the nalysis basic medical research in 2010 nationally for early breastfeeding initiative less than an hour after the baby is born 29,35 percent in East Nusa tenggara 56,52 percent. Government in District TTS had been supporting of early breastfeeding initiative trouhgh regent instruction No : 72/DK/XII/2010, set in SOE in 17 Desember 2010 on the implementatuion of early breastfeeding initiatrive, exclusive breastfeeding and complementary feeding of baby in order to improve the quality of life of children and a decrease in morality rates of infants and toodler in TTS. Based on data from TTS health districts in 2012 number spontaneous labour 6.698 person and 4889 poerson had implemented early breastfeeding inititive or 74 percent. 626 people was born in SOe District hospital, who were born without complication were 300 person and no one implemented early breastfeeding initiative.Objective of this research was to identication the impolementation early breastfeeding initiatives with midwife an to identify breastmilk production with postpartum mother.Method: This research used descriptive method with cross sectional deign, and used total population for sampling.Result: From 35 respondent who succed to implementation early breastfeedimg initiative were 12 person (34,3%) and unsucced were 23 person (65,7%). Breastrmilk production on postpartum mother who l;arge enough are 12 person (34,3%) aqndbreastmil production who not enough are 23 person (65,6%). Mopther who succed with eraly breastfeeding initiative and breastmilk production large enough are 9 person and breastmilk production who notr enough are 3 person. Meanwhile mother who unsucced for earltbreadsfeeding initiative and breastmilk production have large ineough are 4 person and breastmilk production is not enough are 19 person.Conclution: Respondent who succed to implementation early breastfeeding initiatives have breastmilk production large enough. Its because the ability of the baby to sucking breastmilk from their mother.